Prospects and Challenges of Different Delivery Systems in Breast Tumors Therapy - Cunjun Mai; Huiyang Tang; Guie Lai; Lulin Liu; Wenzhen Huang; Kang He; Qingyang Liu; You Sun; Dongmin Yu (Breast Cancer: Basic and Clinical Research)
Breast cancer (BC) is the most prevalent malignancy in women. The emergence of targeted therapies and advancements in comprehensive treatment protocols have significantly improved survival outcomes for patients with early-stage BC. However, individuals with refractory BC, particularly those who have received multiple lines of therapy or presented with distant metastases at diagnosis, continue to face challenges due to the limitations of conventional antibodies and cytotoxic agents in meeting therapeutic needs. Thus, the development of novel and effective treatments for BC, along with strategies to prevent recurrence, remains an urgent priority. Research has shown that nanodrug delivery systems can modify the pharmacokinetic profiles of traditional chemotherapeutic agents, thereby markedly reducing adverse drug reactions. Furthermore, studies have demonstrated that innovative approaches, such as hyaluronic acid-based systems, ultrasound-mediated microbubbles, and antibody-drug conjugates (ADCs), enable targeted and controlled drug release, offering advantages including high drug efficacy, reduced toxicity, and significant antitumor effects. Among these, ADCs have gained increasing attention in BC therapy over recent years. This article provides a comprehensive review of the development and progress of various drug delivery systems in BC treatment, offering an in-depth analysis of their potential applications in clinical practice.